2021
DOI: 10.1016/j.xjon.2021.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after thoracic surgery: Systematic review and meta-analysis

Abstract: The enhanced recovery after thoracic surgery (ERATS) protocol has been shown to reduce complications and hospital length of stay (LOS). [1][2][3] In thoracic surgery, the prototypical ERATS pathway involves a preoperative phase, which focuses on patient education and smoking cessation; the intraoperative phase incorporates multimodal anesthesia along with minimally invasive surgery (video-assisted thoracoscopic surgery [VATS]); and the postoperative phase emphasizes the use of incentive spirometry, early mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…While fast-track protocols have previously been described in thoracic surgery and appeared to show an improvement in patient outcomes, specific ERAS pathways for lung cancer surgery have now been published (2,4,(14)(15)(16)(17)(18) and consistently demonstrate improvements in complication rates, length of stay, readmission rates and costs. A recent meta-analysis has confirmed the benefits of ERAS pathways in this group of patients (19). There are also demonstrable benefits in other metrics following surgery, including opioid use in hospital and subsequently following discharge (16,18).…”
Section: Enhanced Recovery After Surgerymentioning
confidence: 88%
“…While fast-track protocols have previously been described in thoracic surgery and appeared to show an improvement in patient outcomes, specific ERAS pathways for lung cancer surgery have now been published (2,4,(14)(15)(16)(17)(18) and consistently demonstrate improvements in complication rates, length of stay, readmission rates and costs. A recent meta-analysis has confirmed the benefits of ERAS pathways in this group of patients (19). There are also demonstrable benefits in other metrics following surgery, including opioid use in hospital and subsequently following discharge (16,18).…”
Section: Enhanced Recovery After Surgerymentioning
confidence: 88%
“…The review studies regarding the effect of Enhanced Recovery After Thoracic Surgery on specific postoperative pulmonary complications, cost, and patient-reported outcomes such as pain scores and patient satisfaction scores are also warranted. 30 In addition, the use of a comprehensive swallowing evaluation to detect aspiration before initiation of oral feedings after esophagectomy significantly reduced the incidence of pneumonia. This routine swallowing evaluation, incorporated into the postoperative care protocol after esophagectomy, demonstrated that postoperative pneumonia strongly predicted mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Although the contents of Enhanced Recovery After Thoracic Surgery (ERATS) protocols may vary, their use has demonstrated the ability to improve patient outcomes via reductions in length of stay, readmission and postoperative complications [38]. These will ultimately lead to cost savings for healthcare institutions, given that ‘an ounce of prevention is worth a pound of cure’.…”
Section: Postoperative Pain Managementmentioning
confidence: 99%